Advances in high-capacity Li2MSiO4 (M = Mn, Fe, Co, Ni, …) cathode materials for lithium-ion batteries. Issue 119 (19th November 2015) - Girish, H.-N.; Shao, G.-Q.
Abstract : This review highlights the high-capacity Li2 MSiO4 (M = Mn, Fe, Co, Ni, …) cathode materials for lithium-ion batteries. Abstract : The orthosilicate, Li2 MSiO4 (M = Mn, Fe, Co, Ni, …), is a competitive cathode material for next generation high-capacity (∼330 mA h g −1 with a possible 2 Li + extraction per formula unit) rechargeable lithium-ion batteries. It is an alternative to other polyanionic compounds because the raw materials of Fe/Mn-containing oxidates and silica are abundant, cost effective, very safe, environmentally friendly, and its Si–O bond is at least as stable as other polyoxyanion groups with an excellent cycling performance. This review highlights the research progress related to the Li2 MSiO4 cathode materials in terms of the phase transition of the structure, synthetic methods and techniques for improving the electrochemical performance.